Mechanical Performance and Microstructure of Ultra-High-Performance Concrete Modified by Calcium Sulfoaluminate Cement - Meimei Song; Chuanlin Wang; Ying Cui; Qiu Li; Zhiyang Gao (Advances in Civil Engineering)
High autogenous shrinkage property is one of the disadvantages of ultra-high-performance concrete (UHPC), which may induce early age cracking and threaten the safety of concrete structure. In the present study, different dosages of calcium sulfoaluminate (CSA) cement were added in UHPC as an effective expansive binder. Hydration mechanism, autogenous shrinkage property, and compressive strength of UHPC were carried out to investigate the effect of CSA addition on the mechanical properties of UHPC. Scanning electron microscopy was also employed to characterize the intrinsic microstructural reasons relating to the changes in macroproperties. Based on the XRD diagram, increasing formation of ettringite and Ca(OH)2 can be found with increasing CSA content up to 15%. In the heat flow results of UHPC with 10% CSA addition, the maximum heat release increases to 2.6 mW/g, which is 8.3% higher than the reference UHPC, suggesting a higher degree of hydration with CSA addition. The results in autogenous shrinkage show that CSA expansion agent plays a significantly beneficial role in improving the autogenous shrinkage of UHPC. The corresponding autogenous shrinkage of UHPC is −59.66με, −131.11με, and −182.31με, respectively, at 7 d with 5%, 10%, and 15% addition, which is 108%, 117%, and 123% reduction compared to the reference specimen without CSA. In terms of compressive strength, UHPC with 5%, 10%, 15%, and 20% CSA addition has 10.5%, 17.4%, 30.2%, and 22.1% higher compressive strength than that for the reference UHPC at 28 d. Microstructural study shows that there is an extremely dense microstructure in both the bulk matrix and interfacial transition zone of UHPC with 10% CSA addition, which can be attributed to the higher autogenous shrinkage property and can therefore result in higher mechanical performance.